2020
DOI: 10.1002/ijch.201900181
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrole Functionalization by Copper‐Catalyzed Nitrene Transfer Reactions

Abstract: The catalytic functionalization of pyrroles by incorporation of a nitrene group is reported. The Cα-H bond of 1H-pyrrole is amidated upon the formal insertion of the NTs (Ts = p-toluenesulfonyl) group catalyzed by Tp Br3 Cu (NCMe) (Tp Br3 = hydrotris(3,4,5-tribromo-pyrazolyl)borate). N-substituted pyrroles also verify the same transformation. The mechanism proposal is similar to that previously described for benzene amidation with the same catalyst and PhI=NTs, which takes place through aziridine formation, ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The proposed mechanism depicted benzene amidation with the catalyst and PhI=NTs, undergoing via aziridine formation, ring opening and 1,2‐hydrogen shift. A cascade reaction including the coupling of 2,5‐dimethylfuran, 1,2,3‐trimethyl‐pyrrole and a nitrene bunch is clarified prompting a 1,2‐dihydropyridine‐imine compound [69] . Further in 2020, Jiang et al .…”
Section: C−h Functionalization Of Pyrrolesmentioning
confidence: 99%
“…The proposed mechanism depicted benzene amidation with the catalyst and PhI=NTs, undergoing via aziridine formation, ring opening and 1,2‐hydrogen shift. A cascade reaction including the coupling of 2,5‐dimethylfuran, 1,2,3‐trimethyl‐pyrrole and a nitrene bunch is clarified prompting a 1,2‐dihydropyridine‐imine compound [69] . Further in 2020, Jiang et al .…”
Section: C−h Functionalization Of Pyrrolesmentioning
confidence: 99%
“…As a prominent example, nitrene can be applied as a critical reactive intermediate for the synthesis of valuable N-containing molecules, which is mainly generated by the photolysis of various precursors. , However, the direct photolysis of nitrene precursors requires very harsh short-wavelength irradiation, which leads to poor functional group tolerance and competitive photodecomposition processes that diminish the reaction yield. The strategy of indirect excitation with the help of visible-light photocatalysts, for example, polypyridyl complexes of ruthenium or iridium, was used to overcome this problem. In 2011, Liu and co-workers first reported that a nitrene radical anion can be generated by one-electron reduction of the aryl azide, in which [Ru­(bpy) 3 ] 2+ was employed as the photocatalyst .…”
mentioning
confidence: 99%